Deronectes taron sp. n. from the eastern Anatolian region of Turkey (Coleoptera, Dytiscidae, Hydroporinae) - Aykut Medeni̇; Taşar Gani̇ Erhan; Fery, Hans (Zootaxa, 2018)
Deronectes taron sp. n. from the Muş province in the eastern Anatolian region of Turkey is described and illustrated in detail. The species belongs to the D. longipes subgroup of the D. parvicollis species group and resembles in particular D. syriacus Wewalka, 1971. It can be differentiated from this and the other species of the group by the shape of the median lobe which is strongly bent in lateral view. A part of the key to species of the subgroup is updated. Together with the new species the number of the known species of the genus Deronectes Sharp, 1882 is now 59 and that of the longipes-subgroup is 13.